Synthesis, spectroscopic and antimicrobial properties of Co(II), Ni (II) and Cu(II) complexes of (E)-N’-(2-hydroxy -5-nitrobenzylidene)isonicotinohydrazide) - Tolulope M. Fasina; Cordelia U. Dueke-Eze; F. Nneoma Idika (Journal of Applied Sciences and Environmental Management, 2017)
The objective of this study is to investigate the antimicrobial activity of novel Schiff base metal complexes. The resistance of micro-organisms to classical antimicrobial compounds poses a challenge to effective management and treatment of some diseases. In line with this, copper (II), nickel (II) and cobalt (II) complexes of the Schiff base ligand (E)-N’-(2- hydroxy-5-nitrobenzylidene) isonicotinohydrazide) were synthesized and characterized based on elemental analysis, conductivity measurements, infrared and electronic absorption spectroscopy. The results suggest a 1:2 [M:L] stoichiometry for the copper and cobalt complexes and a 1:1 [M:L] ratio for the nickel complex. The electronic absorption spectral data support octahedral geometry for cobalt(II) and copper(II) complexes and square planar for nickel (II). In-vitro antimicrobial properties of the compounds evaluated against five pathogenic bacteria using the agar-well diffusion method revealed that the activity was in the order Ni>Co>Cu. These compounds can be used as substrates for development of new antimicrobial agents.